Youngest Encounter with Gorlin–Goltz Syndrome: Navigating Early Diagnosis and Management - Adarsh Vijayakumar; Rashmi Mary Philip; Sebastian Criton (Indian Journal of Paediatric Dermatology)
Gorlin–Goltz syndrome is a rare autosomal dominant disorder caused by an inactivating mutation of the patched 1 gene. Patients could present as early as infancy with varied presentation and multiple basal cell carcinoma. This case report highlights the youngest reported case to date, a 5-month-old patient, who presented with multiple asymptomatic black papules and dysmorphic features. Dermatoscopy and subsequent investigations including targeted gene sequencing confirmed the diagnosis. This case underscores the importance of early recognition and multidisciplinary approach to the management of Gorlin–Goltz syndrome.